Six weeks of a concurrent training therapy improves endothelial function and arterial stiffness in hypertensive adults with minimum non-responders - Alvarez, C.; Peñailillo, L.; Ibacache-Saavedra, P.; Jerez-Mayorga, D.; Campos-Jara, C.; Andrade, D. C.; Guimarães, G. V.; Gomes-Ciolac, E. [UNESP]; Delgado-Floody, P.; Izquierdo, M.; Gurovich, A. N. (ARAN Ediciones, 2024)
Background: This study aimed to examine the effects of a six-week of concurrent training using high-intensity interval plus resistance training on flow-mediated dilation and pulse wave velocity in hypertensive, elevated blood pressure, or normotensive. A secondary goal was to analyze the inter-individual variability. Methods: A randomized controlled clinical trial was executed with 60 adult participants distributed across six groups: three control groups of hypertensive, elevated blood pressure, or normotensive and other three experimental hypertensive, elevated blood pressure, and normotensive groups, each comprising n = 10 individuals. Participants underwent a six-week intervention of concurrent exercise using high-intensity interval plus resistance training three-weekly. Flow mediated dilation and pulse wave velocity and secondary vascular assessments were conducted before and after the intervention. Results: The hypertensive exercise group exhibited a significant increase in flow mediated dilation (Δ+7.7%; p = 0.003) and a reduction in pulse wave velocity (Δ−1.2 m s−1; p < 0.0001). The normotensive exercise group also showed a significant increase in flow mediated dilation (Δ+8.4%, p = 0.002). Conclusion: The six-week concurrent exercise using high-intensity interval plus resistance training protocol, characterized by its clinical time-efficiency, was effective in improving endothelial function, as demonstrated by increased flow mediated dilation, and in reducing arterial stiffness, indicated by decreased pulse wave velocity.
Seis semanas de terapia mediante ejercicio combinado mejoran la función endotelial y la rigidez arterial de adultos hipertensos con mínimos no-respondedores
Keywords: Arterial hypertension; Arterial stiffness; Blood pressure; Endothelial function; Obesity